Pemberdayaan Pelaku UMKM di Kabupaten Bandung melalui Peningkatan Kapasitas Pemasaran Digital - Erislan, Erislan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This community service activity aims to enhance the marketing capacity of Micro, Small, and Medium Enterprises (MSMEs) in Bandung Regency, particularly in the utilization of digital platforms. Many MSME actors in the region still rely on conventional marketing methods and lack the skills to optimize digital tools for product promotion. In response to this challenge, the program adopted a combination of lectures and group discussions to educate and empower participants. The activity was conducted in February 2025 and involved MSME participants from various sectors such as culinary, handicrafts, and fashion. The lecture session focused on marketing fundamentals, branding strategies, and the use of social media and e-commerce platforms like Instagram, Facebook, and Shopee. Meanwhile, the group discussions enabled participants to share their marketing challenges and exchange practical solutions with peers and facilitators. Results from the activity revealed a significant increase in participants’ understanding of digital marketing concepts. Many participants acknowledged that they had not previously leveraged social media to market their products and found the insights gained during the training to be highly valuable. Additionally, a two-week follow-up session was held to assist participants in implementing their new marketing strategies. This program demonstrates that digital marketing training combined with participatory methods such as discussion can significantly improve the competitiveness of local MSMEs. Ongoing support and similar community engagement initiatives are recommended to ensure long-term impact and to foster sustainable economic growth among MSME actors in rural and suburban areas of Indonesia.